Optimization of Tension Absorption of Geosynthetics through Reinforced Slope - Moayedi, Hossein; Kim Huat, Bujang; Kazemian, Sina; Asadi, Afshin (Electronic Journal of Geotechnical Engineering, 2010)
A series of direct shear tests were carried out on a sandy soil to evaluate the effect of optimum reinforcement orientation through the geosynthetic reinforced slopes. The main aim of the research was to find out how reinforcement should be installed through the shear box with respect to shear plane and regarding to absorbing maximum tension forces. For finding this optimization angle, a large-scale direct shear box was used. The reinforced soil specimens (30.4 × 30.4 × 15.0 cm) were installed through the shear box in five different forms including 0, 30, 45, 60, 90 degree of reinforcement respect to vertical axis of shear box. Based on the results gained from the research, the optimization angle of reinforcement that both shear displacement and soil dilation have caused the most tension stress in dry sandy soils was between 45 and 60 degree with respect to shear failure plane. It was because of the better interaction of the coarse granular soils with geogrid apertures. Finally, a series of two-dimensional finite element simulations were carried out using the results of optimum direction to describe the behavior of reinforced slope under different reinforcement directions with respect to shear failure plane.